From soil aggregates to riverine flocs: a laboratory experiment assessing the respective effects of soil type and flow shear stress on particles characteristics. Issue 13 (23rd July 2013) - Grangeon, T.; Droppo, I. G.; Legout, C.; Esteves, M.
Abstract Particles eroded from hillslopes and exported to rivers are recognized to be composite particles of high internal complexity. Their architecture and composition are known to influence their transport behaviour within the water column relative to discrete particles. To‐date, hillslope erosion studies consider aggregates to be stable once they are detached from the soil matrix. However, lowland rivers and estuaries studies often suggest that particle structure and dynamics are controlled by flocculation within the water column. In order to improve the understanding of particle dynamics along the continuum from hillslopes to the lowland river environment, soil particle behaviour was tested under controlled laboratory conditions. Seven flume erosion and deposition experiments, designed to simulate a natural erosive event, and five shear cell experiments were performed using three contrasting materials: two of them were poorly developed and as such can not be considered as soils, whilst the third one was a calcareous brown soil. These experiments revealed that soil aggregates were prone to disaggregation within the water column and that flocculation may affect their size distribution during transport. Large differences in effective particle size were found between soil types during the rising limb of the bed shear stress sequence. Indeed, at the maximum applied bed shear stress, the aggregated particles median diameter was found to be three times larger for the well‐developed soil than for the two others. Differences were smaller in the falling limb, suggesting that soil aggregates underwent structural changes. However, characterization of particles strength parameters showed that these changes did not fully turn soil aggregates into flocs, but rather into hybrid soil aggregate–floc particles. Copyright © 2013 John Wiley & Sons, Ltd.